BREEDING BIOLOGY OF INDIAN POND HERON BREEDING BIOLOGY OF INDIAN POND HERON BREEDING BIOLOGY OF INDIAN POND HERON Ardeola grayiis Ardeola grayiis Ardeola grayiis IN PUNJAB, INDIA - SUKHBIRPAL KAUR AND TEJDEEP KAUR KLER (The Bioscan, 2018)
Study on breeding biology of Indian Pond Heron was conducted from February to December, 2017 in village Karamgarh (District Barnala) considered as location I and Punjab Agricultural University Campus, Ludhiana as location II. A total of 23 nests were located having clutch size 2 to 5 at both the locations. The overall maximum mean values of egg length 41.61 ± 0.97 mm and 39.08 ± 0.43 mm, egg width 29.71 ± 0.82 mm and 26.15 ± 0.66 mm, egg volume 16.36 cm3 and 11.12 cm3 at location I and II respectively. The average feeding frequency was 1.55 times/hour and 1.63 times/hour at location I and II respectively. Significant positive correlation of egg volume with egg length (r= 0.953) as well as with egg width (r=0.986) at location I was noted; it was not found at location II. There was negative correlation between egg volume and egg shape index (r = -0.259) at location I which was positive (r = 0.144) at location II. Location II which had higher hatching success had attributes like easy food availability due to crop diversity and nesting sites due to presence of indigenous trees.